Forecasting Pada Rantai Pasok Pabrik Penggilingan Daging Menggunakan Metode Time Series - Sri Yunita; Nathwa Alifia Mahesti; Ronald Max Brando Sihaloho; Resad Setyadi (STMIK Budi Darma, 2022)
Meat is one of the livestock products that can hardly be separated from human life because of its nutritional content and can lead to satisfaction or enjoyment for those who consume it, but this is less desirable in consuming meat because of its tough nature, so it is not easy to chew or swallow. Then it will be processed first before finally being consumed. One way of processing, namely by grinding. Meat milling is one of the businesses that aims to meet consumer needs and provide convenience for business actors selling snacks, especially processed meat. The purpose of this study is to determine the supply chain flow of the meat mill and its marketing efficiency and to find out the best forecasting method for planning future production sales. The research method used in this research is the method of forecasting or forecasting. Forecasting is determined using the time series method and the error rate is analyzed using MAD, MSE, and MAPE. The results showed that the supply chain (product flow, flow, and information flow) at the meat mill and its marketing was efficient with a value of 7.12%. As for the results of the best forecasting method, namely least square with the smallest MAPE which is worth 3.3 for consumers and for milled meat processing entrepreneurs of 3.44. With this research, it is hoped that the problems that exist in the field can be identified so that further efforts are made to improve the meat milling supply chain